A review of the feather mite family Gabuciniidae Gaud & Atyeo (Acariformes: Astigmata: Pterolichoidea) of Brazil, with descriptions of eleven new species - Hernandes, Fabio A. (Zootaxa, 2020)
The feather mite family Gabuciniidae currently includes 16 genera and approximately 65 described species associated with birds of nine orders, with the greatest diversity on Accipitriformes. In this study, 11 new species are described from the following hosts: Aetacarus accipiter sp. nov. from the Bicolored Hawk Accipiter bicolor (Vieillot, 1817) (Accipitriformes: Accipitridae), Capitolichus campoflicker sp. nov. from the Campo Flicker Colaptes campestris (Vieillot, 1818) (Piciformes: Picidae), Coraciacarus cabure sp. nov. from the Barred Forest-falcon Micrastur ruficollis (Vieillot, 1817) (Falconiformes: Falconidae), Coraciacarus peixefrito sp. nov. from the Pheasant Cuckoo Dromococcyx phasianellus (Spix, 1824) (Cuculiformes: Cuculidae), Gabucinia neotropica sp. nov. from the Curl-crested Jay Cyanocorax cristatellus (Temminck, 1823) (type host) and C. chrysops (Vieillot, 1818) (Passeriformes: Corvidae), Hieracolichus caboclo sp. nov. from the Savanna Hawk Buteogallus meridionalis (Latham, 1790) (Accipitriformes: Accipitridae), Hieracolichus falcon sp. nov. from the Southern Caracara Caracara plancus (Miller, 1777) (Falconiformes: Falconidae), Piciformobia adjuncta sp. nov. from the Guira Cuckoo Guira guira (Gmelin, 1788) (Cuculiformes: Cuculidae), Proaposolenidia bicolor sp. nov. from the Bicolored Hawk Accipiter bicolor (Vieillot, 1817) (Accipitriformes: Accipitridae), Proaposolenidia plumbea sp. nov. from the Plumbeous Kite Ictinia plumbea (Gmelin, 1788) (Accipitriformes: Accipitridae), and Tocolichus toco sp. nov. from the Toco Toucan Ramphastos toco Statius Müller, 1776 (Piciformes: Ramphastidae). In addition, two new combinations are proposed, Proaposolenidia ostoda (Gaud, 1983) comb. nov. and Aetacarus hirundo (Mégnin & Trouessart, 1884) comb. nov., both transferred from the genus Hieracolichus. With the addition of these new species, the number of gabuciniids described from the Neotropical region has increased from 14 to 25 species. These findings indicate that Brazil is home to a large diversity of undescribed gabuciniids, which is not surprising considering the vast bird fauna of this country, and especially since most avian species from Brazil have yet to be investigated for their feather mites.